1962
DOI: 10.1128/jb.84.4.803-814.1962
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes in Endotoxin Associated With Loss of Biological Potency

Abstract: changes in endotoxin associated with loss of biological potency. J. Bacteriol. 84:803-814. 1962.-The preparation of endotoxins whose gross chemical composition approached that of refined polysaccharide haptenes raised anew the question of which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

1966
1966
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 11 publications
5
21
1
Order By: Relevance
“…The finding of decreased in vitro biological activity in lipid A preparations has also been reported by Nowotny et al (17) and Wahl et al (30) and is most likely due to a general loss of potency observed in LPS preparations having undergone acid hydrolysis (8,20). In addition, we have found that heat treatment markedly decreases the cytotoxic properties of LPS, and since production of lipid A involves boiling for 45 min, this might also explain its loss of potency.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of decreased in vitro biological activity in lipid A preparations has also been reported by Nowotny et al (17) and Wahl et al (30) and is most likely due to a general loss of potency observed in LPS preparations having undergone acid hydrolysis (8,20). In addition, we have found that heat treatment markedly decreases the cytotoxic properties of LPS, and since production of lipid A involves boiling for 45 min, this might also explain its loss of potency.…”
Section: Discussionsupporting
confidence: 89%
“…Both degraded antigens made a line close to the antiserum well. These results are similar to the findings of Ribi et al (8).…”
supporting
confidence: 93%
“…strongly suggest a relationship between the two precipitinogens in LPS-sup. from B. melaninogenicus strain B10 similar to that observed in endotoxin preparations from Enterobacteriaceae by Ribi et al (13) and in Fusobacterium by Kristoffersen (9). This would imply that the rapidly diffusing prccipitinogen corresponds to the so-called "acid hapten".…”
Section: Gel Filtration On Bio-gelsupporting
confidence: 65%